“It makes me feel so much safer”: Sexual and gender minority community perspectives on telehealth use and implications for future practice - Jeffrey A. Wilhite; Lisa Altshuler; Alexa B. D’Angelo; Anna Raykov; Annabelle Abbadessa; Maryam Roosta; Karmen S. Williams; Christian Grov (PLoS ONE, 2026)
Introduction Telehealth has the potential to expand access to care, though barriers including insurance coverage, technology literacy, and personal preferences have been described since the pandemic induced uptick. Sexual and gender minoritized individuals (SGMs) face unique challenges which make telehealth a particularly promising care option. Regardless of population needs, research efforts looking at experiences and opportunities following multiple years of use are missing from the literature. Given that telehealth is here to stay, this study explores telehealth experiences, barriers, and preferences of SGM individuals 4 + years after rapid uptick to inform future efforts for the community. Methods Participants were recruited from an observational cohort study of SGM individuals. Eligible participants consented to follow-up contact and had previously used telehealth. Semi-structured interviews (N = 21) were conducted between March and April of 2024, covering telehealth use, barriers, and future directions. Interviews were recorded, transcribed, and thematically analyzed using a directed content analysis approach informed by prior literature. Coding was completed iteratively by four authors, with themes refined through group consensus, resulting in final recommendations for improving telehealth practice and engagement among SGM populations. Results The majority of participants were White (52%), cisgender men (90%) with at least some college education (90%), employed full-time (73%), and residing in the southern U.S (57%). Participants highlighted telehealth’s benefits, including provider accessibility, convenience, and comfort discussing sexual health needs with affirming clinicians. They found telehealth particularly useful for medication management, mental health, and sexual health services. They also emphasized the importance of promoting telehealth as providing privacy, security, and culturally competent care, findings which underscore their utilization motivators and shed light on unique needs of the population. Participants recommended improvement opportunities, such as creating/expanding directories of LGBTQ + -friendly providers and increasing/tailoring community-targeted marketing through social media and physical spaces. Discussion and conclusion We interviewed a diverse group of SGM-identifying telehealth users to explore their experiences with telehealth-based care. Participants expressed ongoing interest in telehealth overall, but conversations highlighted future opportunities and provided clear next steps for research, practice, and marketing. Our findings provide valuable insight for the next era of telehealth use.